Особливості українського пізньосередньовічного посуду з розкопок укріпленого поселення біля с. Нижньотепле Луганської області - Ключнєв, М.М. (Археологія, 2001)
У статті розглянуто український керамічний посуд доби пізнього середньовіччя з укріпленого поселення XVII—XVIII ст. біля с. Нижньотепле Станично-Луганського р-ну Луганської обл., виділено його основні різновиди, визначено особливості. Поселение у с. Нижнетеплое Станично-Луганского р-на Луганской обл. — пока единственный памятник, имеющий фортификационные сооружения, возведенные по всем правилам военно-инженерного искусства.
В связи с отсутствием прямых архивных свидетельств его существования, археологические материалы — основной источник для исследования данного памятника. Наиболее информативен керамический комплекс, в котором ведущее место занимает украинская позднесредневековая посуда. По функциональному назначению она разделяется на кухонную, столовую и тарную. Имея широкие аналогии среди украинской посуды конца XVII — начала XVIII вв., указанная керамика имеет и особенности, обусловленные прежде всего местным происхождением большинства ее форм. Установлено преобладание кухонной посуды при незначительном количестве остальных ее видов, полное отсутствие поливной керамики.
Доминирование украинской посуды среди керамики поселения указывает на то, что население региона в период заселения края (XVII—XVIII вв.) было носителем традиций украинского гончарства. The settlement near the Nyzhn’oteple village of the Stanychno-Lugansk district of the Lugansk region is a unique late medieval monument in the middle course of the Siverskyi Donets river that has fortifications constructed according to all the rules of military-engineering art.
Since any direct archive evidence for its existence is absent, archaeological materials are the main source for studying the monument. Most informative is the ceramic complex, in which the Ukrainian late medieval utensils play the leading role. For functional purposes, they are divided into kitchen utensils, tableware, and tare utensils. Having broad analogies among the Ukrainian utensils of the end of the XVII — beginning of the XVIII century, the ceramics under study have peculiarities related to, firstly, the local origin of all their forms. We established the prevalence of kitchen utensils under a slight amount of other forms and the full absence of enameled ceramics.
The domination of Ukrainian ceramics among those of the settlement indicates that the population of this region was a carrier of traditions of Ukrainian pottery in the period of settling of the region (XVII–XVIII centuries).